Modern British and Irish criticism and theory : a critical guide - Wolfreys, Julian, 1958- (Edinburgh : Edinburgh University Press, 2006)
A guide to the development of literary theory in Britain and Ireland, this book is aimed at advanced undergraduates, as well as academics working in the field. Beginning with Coleridge and Arnold, it contains essays that address the rise and significance of poetics, and literary and cultural studies. Each essay includes a further reading list.
Preface; 1. Samuel Taylor Coleridge (1772-1834) and Matthew Arnold (1822-1888) -- 2. John Ruskin (1819-1900) and Walter Pater (1839-1894): Aesthetics and the State -- 3. Oscar Wilde (1854-1900): Aesthetics and Criticism -- 4. The Cambridge School: Sir ArthurQuiller- Couch (1863-1944), I.A. Richards (1893-1979) and William Empson (1906-1984) -- 5. James Joyce (1882-1941): Theories of Literature -- 6. Virginia Woolf (1882-1941): Aesthetics -- 7. T.S. Eliot (1888-1965) -- 8. After the C̀ambridge School': F.R. Leavis (1895-1978), Scrutiny (1932-1952) and Literary Studies in Britain.
"First published as part of The Edinburgh encyclopaedia of modern criticism and theory in 2002"--Title page verso
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Criticism -- Great Britain; Criticism -- Ireland; Critique -- Grande-Bretagne.; Critique -- Irlande; LITERARY CRITICISM -- Semiotics & Theory; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Criticism; Great Britain; Ireland; Electronic book